Chemical control of Pogonomyrmex barbatus with corn attractants, in Irapuato, Guanajuato, Mexico - Salas-Araiza, Manuel Darío (2020)
Introduction. Granivorous ants have an economic and ecological impact because they are considered agricultural pests that transport seeds and defoliate cultivated plants. Objective. The objective of this work was to evaluate the effectiveness of the insecticides Imidacloprid and Novaluron in mixture with three cornflour-based attractants for the control of Pogonomyrmex barbatus in field trials in Irapuato, Guanajuato, Mexico. Materials and methods. This research was conducted from August to November 2014, six tratments were considered, the first three consisted of the mixture of Imidacloprid with cornflour (in finely milled pellet, in milled pellet and without pelletizing), the fourth was Novaluron combined with cornflour in milled pellet, and the last two consisted only of cornflour (in finely milled pellet and without pelletizing), in addition to an absolute control. Individuals counts per minute were performed before (reading at 0 h), and after the application of the treatments (readings at 1, 24, 72, 144, and 240 h) on the outside of three anthills previously selected for this purpose. The analysis of variance of the design was completely randomized according to sub-subdivided stripes with three repetitions, and three factors that were the following: six treatments and the absolute control, six readings over time including the count prior to the application of the treatments and the three anthills. Results. There were highly significant statistical differences for the factors: treatments and readings, as well as for the interaction between both. Conclusion. The treatments with insecticide showed their maximum control at 72 h of its application, the best were the Imidacloprid combined with cornflour in two presentations (in milled pellet and without pelletizing), showing greater effectiveness after 24 h of its application.